Mayan phonology. Issue 10 (October 2016) - Bennett, Ryan
Abstract: This paper presents an overview of the phonetics and phonology of Mayan languages. The focus is primarily descriptive, but the article also attempts to frame the sound patterns of Mayan languages within a larger typological and theoretical context. Special attention is given to areas which are ripe for further descriptive or theoretical investigation.